Health Information as "Fodder for Fears": A Qualitative Analysis of Types and Determinants of the Nonuse of Health Information - Link, Elena (Health communication, 2024)
As not all individuals are willing to pay attention to health information it is crucial to understand and distinguish the underlying motives and the scope of various nonuse behaviors. To increase conceptual clarity and specify theoretical assumptions about the types of nonuse of health information and their determinants, we used a qualitative research approach. Semi-structured interviews with 11 female, 10 male, and 10 non-binary participants aged between 18 and 67 (M = 39.7) showed that information ignoring and avoidance are two distinct behaviors characterized by their motivational patterns. Information ignoring is a preference for other content, serving as a strategy to manage limited time resources and receptivity. Information avoidance is understood as a decision to avoid threatening health information serving emotion regulation. Our data further indicate that information ignoring and avoidance are not unidimensional constructs. Instead, the selectivity and consistency of both behaviors build various types of information ignoring and avoidance, which need to be explained differently considering individual differences, cognitive, affective, socio-normative, and structural factors. Further, theory specification should build on the revealed findings and test which factors relate to which kind of nonuse behaviors.